2018
DOI: 10.1177/1471301218788137
|View full text |Cite
|
Sign up to set email alerts
|

Improving advance care planning for care home residents with dementia: Evaluation of simulation training for care home workers

Abstract: The importance of effective advance care planning is often underestimated by professionals caring for care home residents. Using a simulated scenario, this model aimed to highlight the importance of timely advance care planning for care home residents. An adapted simulation effectiveness tool was used to evaluate a simulated scenario of a resident with advanced dementia. Feedback from this tool, N = 28 (response rate 82%), suggests this model was well received and that simulation training delivered by a multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…15 Research indicates that training and education about ACP improved confidence and reduced uncertainty in decision making. 16,17 There are several resources available to support ACP for individuals with dementia and their caregivers. The Alzheimer's Association Dementia Care Practice Recommendations offer updated guidance for dementia care based on a current review of evidence and expert opinion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Research indicates that training and education about ACP improved confidence and reduced uncertainty in decision making. 16,17 There are several resources available to support ACP for individuals with dementia and their caregivers. The Alzheimer's Association Dementia Care Practice Recommendations offer updated guidance for dementia care based on a current review of evidence and expert opinion.…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare providers describe needing a knowledge of dementia, resources and confidence to engage in such discussions 15 . Research indicates that training and education about ACP improved confidence and reduced uncertainty in decision making 16,17 …”
Section: Resultsmentioning
confidence: 99%
“…Using real case scenario, Katwa et al (2020) [ 61 ] evaluated a simulation training for care home workers. This one-day training was well-received by participants, showing benefits of shared learning and a better understanding of multi-disciplinary working with other HPs.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the value to using a defined communication model within the framework of simulation training. 3840 Simulation training is commonly used in undergraduate end-of-life care education for nurses and other disciplines 41 , 42 as it is considered more effective than classroom teaching alone for professional training in addressing complex areas of care and emotionally charged clinical scenarios. 41 , 43 , 44 Simulation training is an educational process that has long been in use in medical student training through the use of Objective Structured Clinical Examinations (OSCEs); simulated scenarios using actors and assessment of the practice of a trainee by qualified doctors.…”
Section: Practice In Rolementioning
confidence: 99%